Application of Balance Score Card as Key Performance Measurement Tool in Assessing the Performance of Deposit Money Banks in Nigeria - Ahmadu, Ladan, Kambari; Nguavese, Nyikyaa Miriam (International Journal of Current Innovations in Advanced Research, 2023)
The banking sector is an integral part of the economy. Hence this sector plays a key role in the wellbeing of the economy. A weak banking sector not only jeopardizes the long-term sustainability of an economy, it can also be a trigger for a financial crisis which can lead to economic crises. The Balanced Scorecard was developed by Robert Kaplan and David Norton in response to the growing need for organizations to accurately design and implement a successful strategic planning and measuring tool which combined the use of financial and non-financial measures. This study examines the application of BSC as key performance measurement tool in assessing the performance of DMBs in Nigeria. Data were collected through the use questionnaire. A total of 50 sets of questionnaire were distributed across ten (10) sampled Bank’s branches in Mararaba and Keffi of Nasarawa State. Chi- square Test analysis tools were used to analyze the result. From the study it was found out that Nigerian Banks are using BSC as tools for measuring performance. It is recommended that more awareness should be carried out to encourage private and public sector in using BSC as a performance measurement tool.